The Impact of an Upgraded Ventilation System on Thermal Comfort in the Newly Renovated UTHM’s Badminton Hall - Teor, Wee Hock; Hariri, Azian (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This study investigates the impact of an upgraded natural ventilation system on thermal comfort within the newly renovated Universiti Tun Hussein Onn Malaysia (UTHM) badminton hall. Achieving sufficient thermal comfort is crucial for occupant performance and well-being, as athletic activities like badminton require a high metabolic rate. Previous assessments indicated that the original ventilation system failed to maintain appropriate indoor environmental conditions. This study aims to evaluate whether the upgraded system, which includes additional exhaust fans, improves thermal comfort. The findings showed that 90% of respondents experienced thermal conditions, with an average TSV of +0.5, that were within or close to the acceptable PMV range of -0.5 to +0.5. Compared to earlier studies, objective measurements indicated a reduction in extreme temperature fluctuations and a moderate improvement in air velocity. However, inadequate airflow persisted in certain localized areas. In conclusion, the upgraded ventilation system has contributed to improving the thermal comfort standards of the UTHM badminton hall. These results provide valuable insights for future enhancements in similar indoor environments and reinforce the importance of proper ventilation design and air flow in naturally ventilated sports facilities.